Use of Power Line Carrier (PLC)Technology Beyond Energy - Wala, Avni (2007)
Power Line Carrier (PLC) is a promising technology that has emerged as an intelligent way to use existing electric grids and in-building power lines for providing additional services to residential as well as commercial consumers. The use of PLC network is not only limited to energy industry, but ranges from enabling provision of internet, and home security systems, to enabling a smart-home where all household appliances can be controlled and operated remotely. This paper analyses PLC technology in more detail. It then goes on to provide recommendations to the owners of the PLC network infrastructure (i.e. the energy companies) as to how they can leverage this huge infrastructure to gain access to new market opportunities.